Use of language across the secondary curriculum - Bearne, Eve, 1943- (Routledge, 1999)
Educational policy is becoming more concerned with the need to ensure that people leave school or college fully literate. We need good oral communicators in the workplace, and being able to understand and respond to different kinds of language is vital in today's society. Included here is a detailed and highly readable account of the ways in which language affects every aspect of study - it crosses all subject boundaries, yet it is commonly seen as the sole responsibility of the English teacher to manage this area of the curriculum. The first section of the book looks at the ideology b.